Integritas dan Corporate Branding pada Tayangan Web Series Solusi BCA - Nabila, Shelly Anisa; Alamiyah, Syifa Syarifah; Winarti, Oktifani (PRoMEDIA, 2024)
AbstractThe era of new media has revolutionized the way we communicate and access information through digital technology. Social media platforms like YouTube play a key role in digital culture by providing easy access for users to share videos. One type of content that has grown on YouTube is the web series, which is similar to TV shows but shorter in duration and divided into several episodes. Web series are now widely used as a communication strategy by many companies, including in Indonesia, which has great potential for development due to the high interest in YouTube. This study analyzes the representation of the value of integrity in the YouTube web series "Nurut Apa Kata Mama," produced by BCA, using John Fiske's semiotic approach. The web series is designed as both an educational tool and a branding strategy, showcasing corporate values such as integrity, teamwork, and customer focus. Through three levels of analysis—reality, representation, and ideology—this study finds that integrity is represented through several characters who demonstrate consistency between words and actions, honesty, and responsibility. This web series strengthens BCA’s corporate branding by presenting the company's identity as an entity that prioritizes integrity in all aspects.Keywords: Representation, Semiotics, Integrity, Corporate branding          Abstraksi Era new media telah merevolusi cara berkomunikasi dan mengakses informasi melalui teknologi digital. Platform media sosial seperti YouTube memainkan peran penting dalam budaya digital dengan menyediakan akses mudah bagi pengguna untuk berbagi video. Salah satu konten yang berkembang di YouTube adalah web series, yang mirip dengan acara TV namun berdurasi lebih pendek dan terbagi dalam beberapa episode. Web series kini banyak dimanfaatkan sebagai sarana strategi komunikasi oleh banyak perusahaan, termasuk di Indonesia yang memiliki potensi besar untuk pengembangannya berkat tingginya minat terhadap YouTube. Penelitian ini menganalisis representasi nilai integritas dalam web series YouTube "Nurut Apa Kata Mama" yang diproduksi oleh BCA, menggunakan pendekatan semiotika John Fiske. Web series ini dirancang sebagai sarana edukasi sekaligus branding, menampilkan nilai-nilai perusahaan seperti integritas, kerjasama tim, dan fokus pada nasabah. Melalui tiga level analisis semiotika John Fiske menghasilkan hasil penelitian bahwa nilai integritas direpresentasikan melalui beberapa karakter tokoh cerita yang menunjukkan kesatuan ucapan dan tindakan, kejujuran, serta tanggung jawab serta pembawaan alur cerita yang membangun hubungan emosional dengan penonton yang mana BCA mengansumsikan brand sebagai manusia yang diringkas dalam web series ini sebagai bentuk memperkuat corporate branding BCA. Kata Kunci: Representasi, Semiotika, Integritas, Corporate branding